The Role of GLP-1 Receptor Agonists in the Management of Polycystic Ovary Syndrome: A Narrative Review - Juszczyk, Angelika; Pietrajtis, Sylwia; Sałapski, Bartłomiej; Brożyna, Dominika; Kubicki, Mateusz; Grębosz, Damian; Piec, Jakub; Komornik, Wiktoria; Łebek, Michał; Lis, Krzysztof (Quality in Sport, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common hormonal disorder among women of reproductive age. Insulin resistance and obesity are frequent components of this syndrome and further worsen the associated hormonal disturbances and infertility. Aim: The aim of this narrative review is to explore the potential role of GLP-1 receptor agonists (GLP-1 RAs) in the management of women with PCOS, with particular focus on their effects on blood glucose fluctuations and excess body weight, both of which are important targets in PCOS treatment. Methods: The literature search was conducted using the PubMed database in order to find articles reporting on the mechanism of action of GLP-1 RAs, the results of their use in PCOS treatment, and their adverse effects. The authors included articles published between 2020 and 2026. Results: GLP-1 RAs exhibit pleiotropic metabolic effects, including the regulation of insulin and glucagon secretion, protective effects on pancreatic beta-cells, and modulation of appetite and energy intake. These mechanisms may contribute to the beneficial clinical outcomes observed in women with PCOS. Current clinical studies and meta-analyses have demonstrated the positive effects of GLP-1 RAs on anthropometric parameters, glucose metabolism, and selected reproductive and hormonal functions, particularly when used in combination with metformin. Adverse effects associated with these agents are mainly gastrointestinal and generally diminish over the course of treatment. Conclusions: GLP-1 RAs appear to represent a promising therapeutic approach for women with PCOS. However, further studies are required to evaluate the long-term effects of their use in this patient population.